THE ROLE OF THE SCO IN FORMING THE CENTRAL ASIAN SECURITY ENVIRONMENT: EOPOLITICAL ASPECTS - SHAIMERGENOV, Timur; TUSUPBAEVA, Gulnar (CENTRAL ASIA AND THE CAUCASUS, 2006)
Of course, it would be too declamatory to maintain that the Central Asian countries are acquiring a special significance in the international relations system, but we cannot deny the increased attention the global actors are focusing on them, mainly due to the geostrategic and eco-nomic potential of the region. The situation is com-plicated by the spasmodic development of certain processes in some of the region’s countries, the roots of which can be found in political and eco-nomic problems, as well as in the abrupt changes that have been occurring in the Central Asian states since the day, they acquired their independence.along with this, a few particularly obvious trends should be noted, including the growing impact of security threats and challenges, which could lead to a dramatic reduction in security in the region and its transformation into what we could call the Asian Balkans. The main reasons for this are the military-political situation in Afghanistan, the aggravated political processes, and the socioeconomic tension in several Central Asian republics. Among the threats which have already be-come traditional, we will note international terrorism, drug trafficking, destabilization, the spread of hostilities to contiguous territories, il-legal migration, and the problem of refugees, the spread of religious extremism, and the possible establishment of military-dictatorial pro-Islamist regimes in the Central Asian states. Along with these, new threats to regional stability and security were manifested in the events of 2005 which drew the increased attention both of the region’s countries and of foreign players—the change in power in Kyrgyzstan and the situation in Andijan. Of course, these events did not cause the situation in Central Asia to spiral out of control, but they were a warning sign to its states and neighbors, giving them reason to think seriously about how to deal with the growing snowball of regional problems. The revved-up integration processes in Central Asia were a reaction to all these threats, with the emphasis on military-political cooperation and ensuring security. After all, due to the transnational nature of these threats and the low level of in-dependence of each of the Central Asian republics, the region’s problems cannot be resolved in isolation. Of course, thanks to the multilateral initiatives of recent years, a regional security system is beginning to form which to some degree is making it possible to overcome certain problems. However, it cannot be said that these processes are yielding effective results. Against this background, we should single out the significance of the Shanghai Cooperation Organization, which is taking unusual approaches toward resolving the problems of the Central Asian countries, including in regional security.according to the SCO member states, the current threats in this sphere come from the five evils:extremism, terrorism, separatism, drug trafficking, and illegal migration of the population. The SCO’s integration efforts are primarily aimed at jointly combating these threats. But at the same time, economic cooperation is gradually beginning to develop within the framework of the Organization.1